The Effectiveness of Reality Group Counseling in Reducing Social Media Dependency - Mirati E. Mooy; Maria Natalia; Joris Taneo (Kuras Institute, 2023)
Social media, a component of the ever-developing science and technology, has positive and negative impacts. One example of its negative impacts is the social media dependency. This dependency is reflected when a person spends excessive time and energy accessing various social media, ultimately affecting his life as a college student. This research sought to determine the effectiveness of reality group counseling in reducing social media dependency. This experimental research employed one group pretest-posttest design. The research samples were selected through a purposive sampling technique by using recruitment criteria, in which the data were collected through a pretest questionnaire named social media dependency scale. The research samples consisted of four college students. The research instrument contained 20 valid statement items with a Cronbach's Alpha reliability level above 0.70. The pretest results showed that the social media dependency was 67.5%, and the posttest revealed the behaviour was 39.5%, meaning there was a 28% decrease in social media dependency. Therefore, it can be concluded that reality group counseling effectively reduces social media dependency.